A IMPROVING LEARNING ACTIVITY USING INTERACTIVE LEARNING MEDIA FOR INFORMATION TEXT MATERIALS OF STUDENTS OF CLASS XII OF SMA NEGERI 3 PALEMBANG: MENINGKATKAN KEAKTIFAN BELAJAR MENGGUNAKAN MEDIA PEMBELAJARAN INTERAKTIF MATERI TEKS INFORMASI KELAS SISWA XII SMA NEGERI 3 PALEMBANG - Ria Ristika; Laila Maharani; Yessi Fitriani (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2024)
This research was conducted due to the lack of student activity in group discussions, lack of enthusiasm in completing assignments, and low use of interactive learning media. This research aims to identify the extent to which the application of interactive learning media can increase student activity in learning, as well as to develop learning strategies that are more effective and in accordance with the characteristics of students at SMA Negeri 3 Palembang. This research method is Classroom Action Research (PTK). Based on the results of classroom action research carried out collaboratively in two cycles, students' activeness in learning Indonesian in Class XII SMA Negeri 3 Palembang can be increased by using interactive learning media. The increase in student activity can be seen from the results of observations which show an increase from 58.75% (fair category) in cycle I to 93% (high category) in cycle II. This success was caused by the use of learning media that facilitated the learning style of each student and provided a few interactive games in cycle II, as well as giving rewards by the teacher. Good teacher interaction and the motivation provided also play an important role in increasing student self-confidence.